Geographical distribution and habitat of Trochillidae (Aves) in the state of Guerrero, Mexico - Sierra Morales, Pablo (2016)
The distribution and abundance of species of Trochillidae family is usually influenced by the flowering and phenology of plants used as a feeding source, mainly in primary forest, so that changes in vegetation cover could impact their populations. We analyzed and characterized the geographical distribution and habitat for 22 species of resident hummingbirds in the state of Guerrero using the vegetation and the land use map of INEGI Series IV (2007-2010). Distribution models were generated with the Genetic Algorithm for Rule Set Production (GARP), using historical records of scientific collections and fieldwork (2001-2009), in combination with climatic and topographic variables. Of the 22 modeled species, six are endemic to Mexico, the same number of species found in a risk category. The highest concentration with regards to richness (14-20 species), endemism (5-6 species) and number of threatened species of hummingbirds (5-6 species) occurred in the biotic province of Sierra Madre del Sur. However, the potential distribution of most of the hummingbirds occurred in disturbed sites or agroecosystems, as a result of changes in land-use. For Campylopterus hemileucurus, Lamprolaima rhami and Heliomaster longisrostris, their potential distribution was highest in areas of primary vegetation. Areas of high hummingbirds presence do not coincide with the Important Bird Areas proposed for bird conservation in Guerrero, considering that, despite its diversity and its extreme popularity, from the conservation perspective hummingbirds have received relatively little attention.